Retorik Penceritaan Dalam HikayatMerong Mahawangsa Narrative Rhetorical in Hikayat Merong Mahawangsa - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Rhetoric is an interesting, fascinating and aesthetic language. Besides that, rhetoric also referring to the use of language that focuses on the effective language skills, politeness and its effective in communicating. The application of rhetoric in a writing or conversation is to persuade or influence the audience. The research will be about the usage of rhetoric in Hikayat of Merong Mahawangsa. The objectives of this study are to discuss the narrative rhetorical techniques and its frequency in Chapter IV, Hikayat Merong Mahawangsa based on Modern Rhetoric Theory (1993). This research is carried out based on Modern Rhetoric Theory (1993) by Enos & Brown. This study also based on a Hikayat Melayu book that was introduced by Siti Hawa (1998) entitled Hikayat Merong Mahawangsa. However, this study only focuses on one chapter from the book which is Islamization Story of King Derbar Raja II and the method used for collecting data is based on text analysis method. Therefore, the findings of the study found that the author of Hikayat of Merong Mahawangsa had applied the narrative rhetorical technique such as situation or event technique, dialogue, monologue, flashback and background of place and community. Hence, it is clear that rhetorical application in producing creative works especially hikayat is able to assure the quality and interesting writing.